(untitled) (World Bulletin of Public Health, 2024)
Many studies report an increase in the frequency of infertile marriages due to the influence of ecology and the environment on the generative function of humans, in particular, chemicalization, radiation, and harmful industrial production. The role of the modern city is emphasized as a complex factor in the growth of infertile marriages, especially in countries with rapid urbanization, due to an increase in the number of women in contact with occupational hazards. One of the most significant factors in the problem of infertility in women is the age of patients over 30 years old, which is a cumulative indicator of the "accumulation" of infertility risk factors.